A method for evaluating the local failure of ultra-high-performance short polyvinyl alcohol fiber-reinforced concrete panels subjected to a projectile impact. Issue 3 (September 2018) - Ueno, Hironori; Beppu, Masuhiro; Ichino, Hiroyoshi; Musha, Hiroyuki; Okamoto, Shuichi
This study investigated local failure characteristics and failure limit thicknesses of an ultra-high-performance fiber-reinforced concrete panel reinforced with polyvinyl alcohol by conducting impact tests. In a series of tests, steel hemispherical projectiles with a mass of 46 g collided with ultra-high-performance fiber-reinforced concrete panels reinforced with polyvinyl alcohol. The ultra-high-performance fiber-reinforced concrete panels reinforced with polyvinyl alcohol with thicknesses in the range of 30–90 mm were tested at the impact velocities of 170–500 m/s. The experimental results revealed that the penetration depth or scabbing damage induced by the impact was significantly suppressed for the ultra-high-performance fiber-reinforced concrete panel reinforced with polyvinyl alcohol compared to that of a plain concrete panel. The experimental results demonstrated that local failure intensity for the panels was similar at equivalent impact energies, regardless of the combination of projectile mass and impact velocity. Based on the test results, we proposed a method for evaluating the penetration depth and scabbing limit thicknesses by the impact energy.